Frequency of Ultrasound Guidance for Vascular Access Placement and Nerve Blocks by Anesthesiologists - Fahad,; Naeem, Kashif; Wanwari, Mahendar; Adeel ur Rehman,; Aziz, Tarique; Hassan, Asif (Indus Journal of Bioscience Research, 2024)
Objective: To determine the frequency at which anesthesiologists utilize ultrasound guidance for the placement of vascular access and nerve blocks.Background : Within the field of anesthesia, anesthesiologists perform vital procedures referred to as perioperative vascular access placement and nerve blocks. Vascular access is crucial for the delivery of fluids and medications required for surgical procedures, whereas nerve blocks offer precise pain control with little systemic effects.Method; A cross-sectional study conducted in tertiary hospitals in Karachi. The study had a duration of six months, commencing on May 29 and concluding on November 29, 2022, following the approval of the Institutional Review Board. The study was conducted with the cooperation of anesthesiology residents and practicing anesthesiologists. The principal researcher sent an email to the anesthesiologists. If there was no response, an additional SMS was sent. If there was no answer, we reached out to the next eligible candidate. Participants who willingly choose to take part answered an online questionnaire. The research proforma was filled out online. Findings: The study comprised 193 participants, which further comprises 47.7% of FCPS consultants, 22.8% of MCPS consultants, 15.5% of FCPS trainees, and 14.0% of MCPS trainees. Ultrasonography guidance was utilised by 49.7% of individuals with 2-13 years of experience and 25.4% of individuals with more than 13 years of experience. The disparity may lack statistical significance. Conclusion: The primary obstacles were the absence of ultrasound equipment, apprehensions over inadequate training, and a propensity to rely on clinical judgement rather than utilizing ultrasonography.